Incremento del ingreso de pequeños agricultores a través de una red empresarial - Arrascue Díaz, Enrique Julián (2011)
This research paper describes the model of business networks and its application to small farmers Networks Bean Valley to improve their competitiveness. THE problem of small firms is not their size but their isolation. Therefore, there is not enough to cluster it is necessary to promote business interaction and promote the association of SMEs by promoting business networking implement joint actions and allow them to seek markets, develop products and implement innovations. It should be noted that trust is an important factor in the process of organizing the network, facilitates the cooperation of its participants and this brings great benefits that are reflected in the economic development of the enterprise network. In fact; discusses the application of the Methodology of horizontal networks of small farmers located in the Valley Bean and its surroundings. The results obtained by the experiments described business networks were positive, able to reduce operating costs, improve processes and increase their income; there is a marked improvement in the competitiveness of each individual company. You got to strengthen the areas of these conglomerates in small farming units, generating economic development and tourism in the path of pineapple in our region La Libertad.